Windows privilege escalation through network backdoor and information mining using USB Hacktool / Hidayat UI Hazazi Ab Wahab and Jasni Mohamad Zain - Ab Wahab, Hidayat UI Hazazi; Mohamad Zain, Jasni (Universiti Teknologi MARA Press (Penerbit UiTM), 2018)
A privilege escalation in the Windows system can be defined as a method of gaining access to the kernel system and allowing the user to have an administrative access to the local admin account system on the computer. This paper describes the proof of concept attack scheme using Universal Serial Bus (USB) Hacktool. The attack scheme, the same interaction on the physical access to the computer system could be accomplished by the attacker using a little effort on social engineering and specialized USB Hacktool to take over the computer system in full where it will collect valuable information and escalate the administrative privilege to gain unauthorized admin access which further attack can be done like setting up an open port for backdoor access. The evaluation of this paper gives a significant value as for educational purpose for proof of concept security project. The implementation on this project could help the responsible team to take necessary action toward physical security access to their computer or workstation.